Dinâmica populacional no Sertão do Rio Pardo (1801-1829) - Oliveira, Marina Costa de [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This paper deals with the population dynamics of the interior part of the Pardo river, the area corresponding to the Freguesia of Nossa Senhora da Conceição da Franca and Rio Pardo, created in 1805, and the Termo de Franca which was raised to the village in 1824, becoming denominate Vila Franca do Imperador. The historical comprises the period from 1801 to 1829 in conjunction with the effective settlement of this territory due to the arrival of paulistas and mineiros. The aim is to deepen our understanding of the population dynamics waged between free - heads of households and non-slaveowners slaveowners - provided free of aggregates and slaves within a context governed by the subsistence economy and domestic supply. It uses the Listas Nominativas de Habitantes the years 1801, 1803, 1805, 1809, 1820, 1824 and 1829; Inventários post-mortem and Registros Paroquiais

Este trabalho trata sobre a dinâmica populacional de parte do sertão do rio Pardo, área correspondente à Freguesia de Nossa Senhora da Conceição da Franca e Rio Pardo, criada em 1805, e ao Termo de Franca o qual foi elevado à vila em 1824, passando a denominar-se Vila Franca do Imperador. O recorte histórico compreende o período de 1801 a 1829, conjugado com o povoamento efetivo deste território em decorrência da chegada de paulistas e mineiros. O intuito é aprofundar o conhecimento sobre a dinâmica populacional empreendida entre livres – chefes de domicílios proprietários de escravos e não proprietários de escravos – livres na condição de agregados e escravos dentro de um contexto regido pela economia de subsistência e abastecimento interno. Utiliza como fontes as Listas Nominativas de Habitantes dos anos de 1801, 1803, 1805, 1809, 1820, 1824 e 1829; Inventários post-mortem e Registros Paroquiais
Keywords: História; Escravidão - História - Brasil; Escravos - Condições sociais; Escravos - História - Franca (SP) - Séc. XIX; Demografia da familia - São Paulo (Estado); População - Historia; Dinâmica populacional; History